Faktor yang Berhubungan dengan Kinerja Perawat di Rumah Sakit Umum Daerah Kefamenanu Kabupaten Timor Tengah Utara - Marcelinus Tulasi; Masrida Sinaga; Yoseph Kenjam (Media Kesehatan Masyarakat, 2021)
The quality of health services is inseparable from the role of medical and non-medical personnel, including nurses. In providing health services, one of the most potential human resources in the hospital are nurses. Good nurse performance is a determining factor for the hospital image in the community. The performance also supports the achievement of organizational goals. Factors affecting nurse performance can be categorized into individual (abilities and skills), psychological (motivation, perceptions, attitudes, personality and learning) and organizational factors (resources, leadership, compensation, workload, rewards, job structure and design). This study aimed to analyze the relationship between motivation, compensation, reward and workload with nurse performance at Kefamenanu Hospital, North Central Timor Regency. This research is an analytical survey with a cross-sectional design. The population in this study consisted of 153 nurses at Kefamenanu Hospital. A total sample of 61 people was selected using a simple random sampling technique. The data were analyzed with the Chi-Square test. The results showed that there was a relationship between motivation (p-value = 0,000), compensation (p-value = 0.002) reward (p-value = 0,000) and workload (p-value = 0.004) with the performance of nurses. The hospital needs to make policies to increase nurse performance such as preparing a proper reward system and balancing the workload.